2016
DOI: 10.1159/000448216
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case of Bilateral Hürthle Cell Adenoma in an Adolescent

Abstract: Background: Hürthle cell (HC) neoplasms are rare among pediatric thyroid cancers. HC adenomas (HCA) are typically benign and localized unilaterally without recurrence, and they are thus treated by hemithyroidectomy. HC carcinomas (HCC) can be bilateral and are more aggressive, necessitating total thyroidectomy. Diagnosis relies upon surgical histopathology demonstrating invasion for classification as HCC or lack of invasion in HCA, since fine needle aspiration fails to differentiate between the two. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…We report the largest cohort of pediatric patients with HCC, and a seven‐year‐old male included in the present series is the youngest patient with HCC described in the literature 1,5‐10 . We confirmed that the relative HCC prevalence of 5.8% detected in our study is very similar to those found in large populations of all ages 8,18 and to other, smaller pediatric cohorts 19‐22 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We report the largest cohort of pediatric patients with HCC, and a seven‐year‐old male included in the present series is the youngest patient with HCC described in the literature 1,5‐10 . We confirmed that the relative HCC prevalence of 5.8% detected in our study is very similar to those found in large populations of all ages 8,18 and to other, smaller pediatric cohorts 19‐22 …”
Section: Discussionsupporting
confidence: 88%
“…HCC differs from its benign counterpart (Hurthle cell adenoma) by the presence of capsular and/or vascular invasion, 8 which have been only sporadically described in young patients with thyroid nodules 1,9,10 . Therefore, Hurthle cell neoplasms are not generally included among the histotypes that may be associated with children's thyroid tumors 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…The Hürthle cell is characterized cytologically as a large cell with abundant eosinophilic, granular cytoplasm and a large hyperchromatic nucleus with a prominent nucleolus. [10] The histopathological diagnostic criteria for HCA of the thyroid are as follows: thyroid tumor cells consist entirely or predominantly (>75%) of follicular cells, characterized by eosinophils [3] and the thyroid tumor tissue has an intact capsule and no vascular invasion. [4]…”
Section: Discussionmentioning
confidence: 99%
“…But it is impossible to judge whether capsule or vascular invasion is present. [3] In addition, HCNs tend to undergo spontaneous necrosis or show extensive degenerative necrosis following fine-needle aspiration biopsy. In these situations, viable lesional cells are often not present, and it is difficult to fully evaluate the lesion pathologically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation